2021
DOI: 10.2147/ott.s289922
|View full text |Cite
|
Sign up to set email alerts
|

TRIM11 Promotes Proliferation, Migration, Invasion and EMT of Gastric Cancer by Activating β-Catenin Signaling

Abstract: Introduction Gastric cancer (GC) is the sixth most common malignant tumor and the third leading cause of cancer-related death in the world. Studies have shown that TRIM protein can regulate transcription factor activity and is associated with many cancers. However, the role of TRIM11 in gastric cancer remains unclear. Methods TRIM11 protein levels were examined in 36 cases of GC tissues and 4 gastric cancer cell lines. TRIM11 overexpression and knockdown cells were cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
17
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 36 publications
6
17
1
Order By: Relevance
“…In line with these results, our results showed that TRIM11 was elevated in most of the GC cases (56.67%) and associated with poor clinical outcomes. In contrast to their report [22], our study revealed that TRIM11 protein expression was an indicator of lymph node metastasis in GC patients. Moreover, we demonstrated that TRIM11 depletion significantly inhibited cell growth and invasion, whereas these were enhanced upon TRIM11 overexpression.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…In line with these results, our results showed that TRIM11 was elevated in most of the GC cases (56.67%) and associated with poor clinical outcomes. In contrast to their report [22], our study revealed that TRIM11 protein expression was an indicator of lymph node metastasis in GC patients. Moreover, we demonstrated that TRIM11 depletion significantly inhibited cell growth and invasion, whereas these were enhanced upon TRIM11 overexpression.…”
Section: Discussioncontrasting
confidence: 99%
“…Several studies have shown that Axin1 protein expression is frequently regulated by proteasomal degradation and that inhibition of Axin1 results in the activation of the Wnt/ β-catenin pathway [36,37]. Moreover, it has been reported that TRIM11 is involved in the activation of the β-catenin pathway via the ubiquitination and degradation of Axin1 in lymphomas [29] and that it promotes cell growth and epithelial-mesenchymal transition in gastric cancer by activating β-catenin signaling [22]. Here, we demonstrated for the first time that TRIM11 binds to Axin1, thus shortening the half-life of Axin1 and leading to activation of the Wnt/β-catenin pathway.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…TRIM family members have attracted more and more attention because of their important roles in cancer. Increasing evidence indicates that TRIM family proteins act as regulators of oncoproteins or tumor suppressor proteins, thus regulating cell growth, migration, metabolism, autophagy, and other biological processes ( 12 , 54 , 55 ). Their abnormal expressions and potential mechanisms have been confirmed in diverse cancers.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that β2-AR is an important effector molecule for chronic stress-mediated adverse effects on tumor progression [8,13,14]. EMT is an important factor affecting tumor invasion and metastasis [15][16][17][18]. In our study, we treated MGC-803 cells with ISO, a nonselective β-adrenergic receptor (βAR) agonist of β2-AR, at different concentrations and found that 20 μM ISO obviously upregulated the expression of β2-AR (Fig.…”
Section: β2-ar Positively Regulates Emt In Human Gastric Cancer Cellsmentioning
confidence: 73%